2016
DOI: 10.1097/ijg.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Choroidal Expansion and Intraocular Pressure Rise During the Water Drinking Test in Healthy Subjects and Patients With Exfoliation Syndrome

Abstract: Choroidal expansion during WDT does not seem to be an important mechanism for IOP elevation in healthy eyes or those with XFS. Furthermore, the similarity of IOP increase to controls suggests that trabecular outflow facility is not impaired in eyes with XFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A recent study [ 23 ] evaluated the change in IOP and ChT after the WDT in patients with pseudoexfoliation syndrome. Researchers used the EDI technique on an SD-OCT and documented the choroidal change exclusively in the subfoveal area.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 23 ] evaluated the change in IOP and ChT after the WDT in patients with pseudoexfoliation syndrome. Researchers used the EDI technique on an SD-OCT and documented the choroidal change exclusively in the subfoveal area.…”
Section: Discussionmentioning
confidence: 99%
“…This was not surprising given two separate proposed mechanisms. The difference between maximum and minimum measurements on the water drinking test is thought to represent a physiological change (such as in outflow facility 36–38 or choroidal expansion, 39 although this remains debated 40 ) in response to osmotic stress. In comparison, the daily range measured using the iCare HOME or phasing is thought to indicate the individual's variation with (such as treatments 5 ) or without a specific external stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the similarity of IOP increase in PXS and control eyes, authors suggested that trabecular outflow facility is not impaired in eyes with PXS. 23 …”
Section: Discussionmentioning
confidence: 99%